Falls Protocol - Wibowo, Catur Prasetyo; Jufan, Akhmad Yun; Wisudarti, Calcarina Fitriani Retno (Jurnal Komplikasi Anestesi, 2018)
Fluid therapy in the emergency case, especially shock is usefull for the patient, but it can be detrimental if we give it too much. There is so many type of shock, and fluid therapy is not the answer for all type of shock. FALLS-protocol (Fluid Administration Limited by Lung Sonography) was designed so that there is guidance for fluid therapy on shock patient. FALLS-protocol follows weil’s classification of shock. It uses simple equipment (ultrasonography) and microconvex probe that can be used to assess heart, lung, and vascular. Right now, the ultrasonography is so well known in the emergency setting.